THE WEAVER: A CASE OF METASTATIC CANCER IN HUACA POTOSI, VALLEY RIMAC - Sullca, Arelí (2015)
In 2003 conducted excavations in the mounds 18 and 19 complex Maranga, Rimac Valley, by archaeologist Carmen Gabe. During this excavation was found in the two northern platform mound 19 a funeral context 5 burials. Subsequently, desenfardo one of these burials, which corresponded to a weaver was performed, however, due to the features, both physical (pathological features) and its grave goods, It is likely being treated for an individual who enjoyed a high social status within their society. This article is the result of a bioarchaeological analysis of this case and that led to a severe injury pathological outcome of metastatic cancer, which would correspond to one of the few found in the Lima area during the Late Horizon period.